“Difficult to Flush Chemoport: An Important Clinical Sign” - Sundriyal, Deepak (Indian J Surg Oncol, 2014)
A central venous access device is an intravenous device whose internal tip lies in a large central vein. Chemoport is a central venous device which serves various purposes in oncology practice apart from optimum delivery of chemotherapy. Various early and late complications have been frequently reported with the use of these devices. Fracture-embolization of the port catheter is an uncommon but life-threatening complication. Timely recognition and management is important to minimize the morbidity and mortality.